Optimising the Yield and Distribution of Effective Explosion Energy in Fans and Rings of Blastholes (The Australasian Institute of Mining and Metallurgy, 1988)
The cost-effectiveness of blasts involving radiating blastholes is cur- rently restricted in the following ways. (a) Significant percentages of potential explosion energy are not being liberated; the collar sections of some charges are being dislocated and/or desensitised by the detonations of adjacent earlier-firing charges. (b) If the minimum charge spacing is too small, detonation of an early- firing charge can initiate an adjacent charge sympathetically, thereby eliminating the benefit of any intended inter-charge delay. (c) The overall distribution of energy is poor. Appreciably better fragmentation would be achieved if current drill- ing patterns were to be replaced by staggered fans/rings having a toe spac- ing : burden ratio of about 4 : 1. This wide-spaced pattern would enable a higher percentage of the potential energy to be released, would reduce the incidence of sympathetic detonation and would provide a superior overall distribution of this liberated energy. If improved fragmentation is not required, the proposed fan/ring design should allow a significant expansion of the blasthole pattern with consequential cost savings in drill- ing, explosives and initiation.